Trabalho doméstico remunerado na velhice: significados e sentidos trazidos pelas empregadas domésticas em Toledo – PR (2020-2024) - Berdague, Veronica Marques da Costa (2024)
The research focuses on an investigation into the meanings of work for paid domestic workers over the age of 50 who entered the world of domestic labor during their childhood or adolescence. The objective is to explore the relationship these women establish between their domestic work performed since childhood and their current experiences, as well as how they perceive their work across different periods of their lives. Additionally, the study aims to elucidate their future expectations. The research seeks to identify the cultural and socioeconomic determinants of early entry into domestic work, the challenges faced, the opportunities denied or neglected, and the consequences of domestic labor on their lives. It is situated within the field of oral history, where the primary focus is not just on the narrated event itself but on how the individual remembers and interprets it. In this approach, the way participants recount their stories becomes the true object of study in orality. Thus, employing this methodology helps in understanding the processes through which people construct meanings and significance, allowing the researcher to immerse themselves in the experiences and ways of thinking and acting of the subjects regarding the investigated theme. In the case of domestic workers, the aim is not only to corroborate what socioeconomic data reveal but also to highlight the experiences and meanings these women attribute to the work to which they have dedicated their youth and possibly a significant part of their old age.